SIMPLE ACCOUNTING TRAINING FOR OPTIMIZING FINANCIAL RECORDING OF BATIK GEMPOL MSMEs: PELATIHAN AKUNTANSI SEDERHANA UNTUK OPTIMALISASI PENCATATAN KEUANGAN UMKM BATIK GEMPOL - Nizar, Muhammad; Rakhmawati, Antin; Rakhmawati, Nora (Darmabakti Cendekia: Journal of Community Service and Engagements, 2025)
Background: Many micro, small, and medium enterprises (MSMEs) still face challenges in financial recording, which affects cash flow management and access to capital. Objective: This community service activity aims to enhance the understanding and skills of financial recording for Batik Canting Cantik MSMEs in Gempol, Pasuruan, through simple accounting training. Method: The method used is Participatory Action Research (PAR), which includes socialization, interactive training, financial recording demonstrations, and direct mentoring. The partners involved are batik entrepreneurs in Gempol, Pasuruan. Evaluation is conducted through pre-tests and post-tests to measure the improvement of participants' understanding. Results: This activity showed a 53% increase in financial recording understanding, a 77% improvement in the ability to prepare profit and loss statements, and a 65% rise in daily transaction recording practices. Some challenges encountered include a lack of disciplined recording habits, mixing business and personal finances, and limited access to digital recording technology. Conclusion: This training effectively enhances MSMEs' financial literacy. The solutions provided include simple accounting books, digital modules, and additional mentoring sessions. It is expected that more systematic and accountable financial recording will support the sustainability of partner businesses.